2003
DOI: 10.1073/pnas.0836098100
|View full text |Cite
|
Sign up to set email alerts
|

Telomere attrition and Chk2 activation in human heart failure

Abstract: The ''postmitotic'' phenotype in adult cardiac muscle exhibits similarities to replicative senescence more generally and constitutes a barrier to effective restorative growth in heart disease. Telomere dysfunction is implicated in senescence and apoptotic signaling but its potential role in heart disorders is unknown. Here, we report that cardiac apoptosis in human heart failure is associated specifically with defective expression of the telomere repeatbinding factor TRF2, telomere shortening, and activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
153
0
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(172 citation statements)
references
References 43 publications
14
153
0
5
Order By: Relevance
“…Accordingly, over-expression of TRF2 showed protective effects in terms of oxidative stress induced apoptosis. 36 On the other hand, chondrocytes and other somatic cells 37 were shown to enter a senescent state in spite of abundant TRF expression. Oxidant insult causes DNA base alterations and thus changes telomere sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, over-expression of TRF2 showed protective effects in terms of oxidative stress induced apoptosis. 36 On the other hand, chondrocytes and other somatic cells 37 were shown to enter a senescent state in spite of abundant TRF expression. Oxidant insult causes DNA base alterations and thus changes telomere sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Chk2 is involved in the DNA damage signal transduction pathway between ATM and p53, and is phosphorylated/activated by ATM upon DNA damage or threshold levels of telomeres (DiTullio et al, 2002;Fagagna Fd et al, 2003;Oh et al, 2003). The widespread Chk2 activation observed in cervical carcinomas represents the presence of DNA damage and genetic instability (DiTullio et al, 2002).…”
Section: Telomere Attrition In Cervical Carcinogenesismentioning
confidence: 99%
“…In vitro studies of human cultured cells indicate that critically shortened telomeres mimic double-stranded DNA breaks (DSBs), thereby activating the DNA damage response through the ATM-p53 pathway (Karlseder et al, 1999;Pandita, 2002). Since Chk2 is an essential mediator between ATM and p53, and its activation occurs upon telomere shortening in senescent human fibroblasts and heart failure (DiTullio et al, 2002;Fagagna Fd et al, 2003;Oh et al, 2003), we thus sought to determine whether and how the DNA checkpoint responded to telomere erosions in precursor and malignant lesions by assessing the phosphorylated Chk2 at Thr68. There was no detectable phosphoryla- tion of Chk2 protein in normal areas of all the samples, whereas a positive staining was seen in 11/20 of CINs and 9/10 of invasive cancers, respectively, which suggests a constitutive activation of the DNA damage response pathway.…”
Section: Telomere Attrition In Cervical Carcinogenesismentioning
confidence: 99%
“…To substantiate the role of ROCK-1 in this proteolytic cascade process in vivo, ROCK-1-null mice, which are viable (15), were subjected to severe pressure overload as a pathophysiological signal for apoptosis (15,20). Consistent with the siRNA results, we found that ROCK-1 ĻŖ/ĻŖ mice exhibited significantly reduced TUNEL-positive cardiac myocytes (46 myocytes per 10 5 nuclei) compared with WT mice (93 myocytes per 10 5 nuclei, P Ļ½ 0.05) when subjected to pressure overload through aortic banding for D and E).…”
Section: Rock-1 Knockout Prevented Apoptosis Induced By Ceramide In Cmentioning
confidence: 99%